Sonographic assessment of hand and wrist tendons abnormalities - Asmaa Hussein Habib; Hatem Mohamed El-Azizi; Salma Hesham Hefny; Omar Mohammed Nouh (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Tendons of the hand and wrist are the seat of different types of pathologies that might be attributed to degenerative changes, inflammation, or even rupture. All of which can significantly impair hand functions and hence, the quality of life. Ultrasound can help diagnose a wide spectrum of tendon abnormalities and direct the surgical management in operable cases saving time and effort. The aim of this work was to evaluate the role of ultrasound in the assessment of different tendon pathologies in the hand and wrist and correlate imaging findings with clinical and operative data (in operable cases). Methods The study was conducted on 33 patients who presented with different tendon pathologies. After thorough history taking and clinical examination, US examinations were performed to both the affected and healthy hands. Continuity of the tendon, possible cause of restricted mobility, swellings as well as presence or absence of adhesions, tears, or associated vascular injury or retained foreign bodies were assessed. In operable cases, the surgery team provided feedback regarding the operative findings to correlate them with the US findings. Results The study included 33 patients; 20 males and 13 females, the majority of hand or wrist tendon abnormalities were encountered due to trauma, In this study flexor tendons were the most affected at 84.8% and 15.2% for extensors. US was used to diagnose trigger finger in 20.7%, adhesions at 6.9% of cases, tendon tears in 63.6% of study population. In flexor tendon tears, ultrasound and surgery findings were consistent with regard to the gap distance regarding in both the Flexor digitorum profundus and Flexor digitorum superficialis (FDS and FDP); with strong positive correlation between them (r = 0.995, and 0.959 respectively). Conclusion Ultrasound serves as an excellent diagnostic modality for assessment and management of various hand and wrist tendon abnormalities. It can pinpoint the exact site and nature of tendinopathy. This can guide clinicians in the management plan.